2019
DOI: 10.1111/obr.12931
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Public Health/Pediatric Obesity interventions on socioeconomic inequalities in childhood obesity: A scoping review

Abstract: SummaryChildhood obesity has a strong social gradient. This scoping review aims to synthesize the evidence on the impact on inequalities of non‐targeted interventions to reduce the prevalence of childhood and adolescent obesity in high‐income countries. We updated a review by Hillier‐Brown, searching up to 31 December 2017 on MEDLINE, Embase, The Cochrane Library, CINAHL, and PsycINFO, with no limitations on study design. Fifty‐eight studies describing 51 interventions were included: 31 randomized clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 80 publications
0
34
0
6
Order By: Relevance
“…Una consideración necesaria es que los programas de prevención no incrementen las disparidades, es decir, que favorezcan especialmente a los grupos que presentan menores factores de riesgo y, por tanto, menor prevalencia de obesidad 45 . La respuesta homogénea en los últimos tres años de los tres centros en nuestra muestra, con diferente representación socioeconómica, es un indicador indirecto de ausencia de este efecto.…”
Section: Discussionunclassified
“…Una consideración necesaria es que los programas de prevención no incrementen las disparidades, es decir, que favorezcan especialmente a los grupos que presentan menores factores de riesgo y, por tanto, menor prevalencia de obesidad 45 . La respuesta homogénea en los últimos tres años de los tres centros en nuestra muestra, con diferente representación socioeconómica, es un indicador indirecto de ausencia de este efecto.…”
Section: Discussionunclassified
“…This is likely to be challenging for many families but particularly difficult in families from lower SES backgrounds; this may act to further widen the health inequalities apparent with obesity [30]. A recent review indicated that all intervention types risk widening health inequalities but complex interventions which are targeted at multiple levels (systems, community, individual) and in multiple settings (school, health, population) appear to have less negative effects, and fiscal measures may even bring benefits [31]. Successive UK governments' policies highlight obesity as a serious problem; however there is a political tension between state and individual responsibility.…”
Section: Plos Onementioning
confidence: 99%
“…Though this might be included in other categories, it is listed separately due to the considerable attention it has gained in previous research. [33][34][35][36][37][38][39] These school-level determinants were examined for their impact on numerous health outcomes. The outcomes most often focused on include alcohol consumption, smoking and substance use, 20 29-31 40 eating behaviour and obesity, 35 36 38 41 42 behavioural and conduct problems, 20 31 43 or physical activity and sedentary behaviours.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…These school-level determinants were examined for their impact on numerous health outcomes. The outcomes most often focused on include alcohol consumption, smoking and substance use, 20 29–31 40 eating behaviour and obesity, 35 36 38 41 42 behavioural and conduct problems, 20 31 43 or physical activity and sedentary behaviours. 33 34 37 39 41 …”
Section: Introductionmentioning
confidence: 99%